Incidence and prognosis associated with troponin elevation after cardiac surgery: a prospective cohort study - Arthur Clement; Lee S Nguyen; Anousone Daulasim; Magali Souibri (BMJ Open)
Objective Cardiac troponin is used as a prognostic biomarker after cardiac surgery. However, numerous confounding elements, such as inflammation, liver and renal function biomarkers, have been associated with troponin variations. Furthermore, several thresholds regarding the definition of myocardial infarction have been suggested. We aimed to confirm the accuracy of troponin, analysed as time-dependent variable, to predict mortality independently from other biomarkers; and to assess the incidence and prognosis of a 10 times upper normal value threshold (troponin10N) used in the current fourth definition of myocardial infarction.Methods In a prospective cohort of patients who underwent cardiopulmonary bypass cardiac procedures, we assessed the association between serum levels of troponin, creatinine, bilirubin, serum glutamic-oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), C-reactive protein (CRP), lactate and in-hospital mortality. Several models were tested, including time-dependent Cox regression, survival and latent class analyses. Repetitive measurements were accounted for.Results We included 3857 patients. In-hospital mortality was 2.8%. Troponin was independently associated with mortality in all models, after adjusting for other biomarkers. Of note, troponin10N was reached in 3830/3857 (99.3%) of patients. Similarly, renal function was independently associated with mortality. Conversely, CRP and liver biomarkers were not associated with mortality, once adjusting for other confounders.Conclusion We confirmed that troponin increase was independently associated with mortality after cardiac surgery. This association was independent of inflammatory syndrome and renal and liver failure. Troponin10N was reached in almost all patients, questioning the relevance of this criterion to define postoperative myocardial infarctions after cardiac surgery.